Conceptualising and managing supervisory drift. (10th December 2021) - Roscoe, Jason
Abstract: Clinical supervision is widely considered to be an essential component in the translation of evidence-based treatment protocols into routine clinical practice. Experts in the field have produced guidance on the structuring of CBT supervision, yet previous surveys on everyday practices have consistently found that supervisors and supervisees appear to drift from these recommendations. Surprisingly, little has been written on the origins and maintenance of supervisory drift and thus it remains a poorly understood phenomenon. To assist supervisors, supervisees and meta-supervisors in recognising and responding to signs of drift, this paper seeks to build on the understanding of therapist drift by conceptualising how supervisor and supervisee cognitions, emotions and behaviour could intentionally or unintentionally render the supervision process ineffective or at worst harmful. Drawing on therapist schema literature, hypothesised pre-disposing factors for drift are presented together with clinical examples and a range of steps for managing indicators of drift in practice. Further research is needed to gather empirical support for the mechanisms proposed. Key learning aims: As a result of reading this paper, readers should: (1) Understand what supervisory drift is and the various forms it might take. (2) Recognise some of their own behaviours within supervision which might affect the quality and effectiveness of supervision. (3) Identify ways in which problematic elements of supervision could be addressed within supervision, or supervision of supervision (SoS), through the use of a bespoke formulation and action-based methods.